Benefit analysis of service quality degradation: A case study of the tourism industry. Issue 8 (17th November 2017) - Hsieh, Li-Yang; Lin, Su-Mei; Lee, Yao-Hsien
Abstract: During economic depression, improving profits to respond to the current economic crisis is highly crucial for both the regional and national tourism businesses. The operating cost structure of the tourism industry involves high fixed costs and low variable costs. Therefore, cost-based pricing cannot increase the profit of businesses in this industry; alternatively, value-based pricing is required to increase profits. According to the product quality discrimination model implemented in previous studies, artificially degrading the quality or functions of products enables businesses to register maximized profits. This paper examines the benefits of degrading hotel landscape service quality levels in the tourism industry in improving profits. The examination results reveal that when the market size remains unchanged and when the original quality level of high-quality services is maintained, quality discrimination enables businesses to improve their profits.